Variability in the time to initiation of CPR in continuously monitored pediatric ICUs. (June 2018) - Olson, M.; Helfenbein, E.; Su, L.; Berg, M.; Knight, L.; Troy, L.; Sacks, L.; Sakai, D.; Su, F.; ,
Abstract: Aim: To study the influence of patient characteristics and unit ergonomics and human factors on the time to initiation of CPR. Methods: A single center study of children, 0 to 21 years old, admitted to an ICU who experienced cardiopulmonary arrest (CPA) requiring >1 min of chest compressions. Time of CPA was determined by analysis of continuous ECG, plethysmography, arterial blood pressure, and end-tidal CO2 (EtCO2 ) waveforms. Initiation of CPR was identified by the onset of cyclic artifact in the ECG waveform. Patient characteristics and unit ergonomics and human factors were examined including CPA cause, identification on the High-Risk Checklist (HRC), existing monitoring, ICU type, time of day, nursing shift change, and outcome. Results: The median time from CPA to initiation of CPR was 50.5 s (IQR 26.5 to 127.5) in 36 CPAs. Forty-seven percent of patients experienced time from CPA to initiation of CPR of >1 min. There was no difference in CPA cause, ICU type, time of day, or nursing shift change. Conclusion: Nearly half of pediatric patients who experienced CPA in an ICU setting did not meet AHA guidelines for early initiation of CPR. This is an opportunity to study the recognition phase of CPA using continuous monitoring data with the aim of improving the understanding of and factors contributing to delays in initiation of CPR.